A developer's guide to SQL server 2005 - Beauchemin, Bob (Microsoft .NET development series., 2006)
"I come from a T-SQL background, so when I first laid my eyes on SQL Server 2005, I was shocked--and then, I was scared! I didn't have a CLR or XML background and suddenly had an urgent need to learn it. SQL Server 2005 is too big of a release to learn from the books online. Fortunately, now there is a book for developers who need to go from SQL Server 2000 to SQL Server 2005 and to do it as painlessly as possible. Basically, it's one-stop shopping for serious developers who have to get up to speed quickly. I'll keep this one on my desk--not on my bookshelf. Well done, Bob and Dan!"--Dr. Tom Moreau SQL Server MVP and Monthly Columnist SQL Server Professional, Brockman Moreau Consulting Inc. "A SQL book truly for developers, from two authorities on the subject. I'll be turning to this book first when I need to understand a component of SQL Server 2005." --Matt Milner Instructor Pluralsight "An excellent book for those of us who need to get up to speed on what's new in SQL Server 2005. The authors made sure this book includes the final information for the release version of the product. Most other books out now are based on beta versions. It covers key areas from XML and SQLCLR to Notification Services. Although the wide variety of information is great, my favorite part was the advice given on when to use what, and how performance is affected." --Laura Blood Senior Software Developer Blue Note Computing, Inc. "SQL Server 2005 is a massive release with a large number of new features. Many of these features were designed to make SQL Server a great application development platform. This book provides comprehensive information about the SQL Server features of most interest to application developers. The lucid text and wealth of examples will give a developer a clear understanding of how to use SQL Server 2005 to a whole new class of database applications. It should be on every SQL Server developer's bookshelf." --Roger Wolter Solutions Architect Microsoft Corporation "While there will be a lot of good books on SQL Server 2005 development, when people refer to the 'bible, ' they'll be talking about this book." --Dr. Greg Low Senior Consultant Readify Pty Ltd "SQL Server 2005 is loaded with new features and getting a good overview is essential to understand how you can benefit from SQL Server 2005's features as a developer. Bob and Dan's book goes beyond enumerating the new SQL Server 2005 features, and will provide you with lots of good examples. They did a good job striking a balance between overview and substance." --Michiel Wories Senior Program Manager, SQL Server Microsoft Corporation Few technologies have been as eagerly anticipated as Microsoft SQL Server 2005. Now, two SQL Server insiders deliver the definitive hands-on guide--accurate, comprehensive, and packed with examples. A Developer's Guide to SQL Server 2005 starts where Microsoft's documentation, white papers, and Web articles leave off, showing developers how to take full advantage of SQL Server 2005's key innovations. It draws on exceptional cooperation from Microsoft's SQL Server developers and the authors' extensive access to SQL Server 2005 since its earliest alpha releases. You'll find practical explanations of the new SQL Server 2005 data model, built-in .NET hosting, improved programmability, SQL:1999 compliance, and much more. Virtually every key concept is illuminated via sample code that has been fully updated for and tested with the shipping version of the product. Key coverage includes Using SQL Server 2005 as a .NET runtime host: extending the server while enhancing security, reliability, and performance Writing procedures, functions, triggers, and types in .NET languages Exploiting enhancements to T-SQL for robust error-handling, efficient queries, and improved syntax Effectively using the XML data type and XML queries Implementing native SQL Server 2005 Web Services Writing efficient, robust clients for SQL Server 2005 using ADO.NET, classic ADO, and other APIs Taking full advantage of user-defined types (UDTs), query notifications, promotable transactions, and multiple active result sets (MARS) Using SQL Management Objects (SMO), SQL Service Broker, and SQL Server Notification Services to build integrated applications